Lexical consistency in the Holy Quran for economic verses: A textual study - Nasiri, Dr. Rohollah; Al-Nashi, Prof Dr. Muayad Mahdi; Awaid, Mustafa Khalaf (Thi Qar Arts Journal, 2023)
This research deals with a linguistic study represented by the lexical coherence of the selected economic verses. Linguistics of the text is one of the most prominent linguistic sciences that has taken upon itself the task of studying the text, and has dealt with the text as a whole structure and not an arbitrary pavement of words and sentences. The task assigned to text linguistics is to link the text and its components to external elements through a set of textual criteria proposed by de Bo Grand. These criteria came to encompass all definitions that dealt with the text in its diversity, and represent the actual basis for finding texts and using them, namely: coherence, cohesion, acceptability, informativeness, intentionality, situationality, and intertextuality. De Bo Grand’s theory appeared in 1981 AD; as linguistic studies carried out by American and European schools interacted with various sciences, including linguistic and non-linguistic. Coherence is considered the main factor among the factors that achieve textuality for the text, as it is a tightening of verbal or formal relationships distributed between parts of the text through weaving a network of relationships that link the surface structure of the text in a way that makes it an integrated and consistent linguistic unit, and it is based on two aspects: lexical coherence and syntactic coherence. Each contributes to linking parts of the surface text. This research will focus on lexical coherence, which is a formal means that works on referential linking at the level of the lexicon, giving meaning its continuity by relying on the lexicon and its vocabulary that are related to something mentioned, and then employing it on economic texts of the Holy Quran; which would reveal the overall unity of economic texts and their cohesion. The research indicated that lexical coherence has a great role in linking economic texts to the linguistic system, its originator, and its recipient in order to achieve a comprehensive vision for these texts. Since the Qur’anic text is the clearest text in Arabic language where features of textual cohesion appear; because it is God’s miraculous speech, economic texts were distinguished by their strong grammatical cohesion between their parts, which made them a wide area for study.